Kecerdasan Emosional Menurut Luqman Al-Hakim (Studi Analisis Surat Luqman, Ayat 12 – 19) - Moh Mansur Fauzi (JURNAL PENDIDIKAN ISLAM AL Iâ€™TIBAR, 2017)
Loss of sense of trust, moral damage, rampant fight among students are the dynamics of education in the country. Declining quality of education not only from the ordinary, but also from the elite. Corruption, abuse of commission, drugs, drunkenness are phenomena that we often hear and are no longer taboo for us to witness. By teaching emotional intelligence in educational institutions and not overly elevating IQ is a solution at the moment. The balance of IQ, EQ, and SQ needs to be taught again, with the appearance of Luqman al-Hakim known for his wisdom. We can learn some lessons from him, such as how to investigate the adolescent of this nation properly.